1987
DOI: 10.1007/bf00195605
|View full text |Cite
|
Sign up to set email alerts
|

Cross reactivity of anti-epithelial membrane antigen monoclonal for reactive and neoplastic glial cells

Abstract: An anti-epithelial membrane antigen monoclonal (Clone E29) was used as part of a panel of antisera in the investigation of primary CNS and metastatic tumours. In contrast to others, definite and often strongly positive cross-reactivity has been demonstrated on glial cells. The material consisted of fourteen astrocytomas, two ependymomas, six cerebral metastases and two cases of gliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…It is mainly confined to the luminal membrane of normal glandular epithelium (29) and is a good marker of epithelial differentiation (9). EMA positivity in ependymomas has been observed by some investigators (6,12) but others have reported negative results (25,29). Only one tumour in our study showed immunoreactivity to EMA.…”
Section: Discussionsupporting
confidence: 49%
“…It is mainly confined to the luminal membrane of normal glandular epithelium (29) and is a good marker of epithelial differentiation (9). EMA positivity in ependymomas has been observed by some investigators (6,12) but others have reported negative results (25,29). Only one tumour in our study showed immunoreactivity to EMA.…”
Section: Discussionsupporting
confidence: 49%
“…To our knowledge, up until 1986 EMA had not been identified in normal nervous tissue (Ellis et al, 1984) nor i n neuroectodermal brain tumours; including cells in two ependymomas (Sloane & Ormerod, 1981;Cordell et al, 1985). However, in a more recent report (Hitchcock & Morris, 1987), reactive and neoplastic glial cells, including cells i n two ependymomas, were shown to be positive for EMA.…”
Section: Introductionmentioning
confidence: 82%
“…A three-layer immunoperoxidase technique for paraffin sections was used with the monoclonals to vimentin (VIM), cytokeratin (CK) as detailed previously [10]. The same tissue preparation was used for detecting Desmoplakin I & II using a biotin streptavidin technique.…”
Section: Methodsmentioning
confidence: 99%